The gendered effects of climate shocks on labour and welfare in Zambia - Alessandra Hidalgo-Arestegui; Patricia Justino; Gabriel Facundes Monteiro; Rodrigo Carvalho Oliveira; Bruce Sianyeuka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper exploits several waves of two major nationwide representative surveys to document the impacts of climate shocks on individuals and households in Zambia. We merge these datasets with historical precipitation and temperature data at the district level. First, we show the gendered effects of the shocks, which have a higher negative impact on women. Women have a lower probability of being in the labourforce and fewer hours of work when experiencing shocks. Second, we show that households affected by climate shocks have 16% lower consumption, which is mainly explained by female-headed households. We show that social protection policies mitigate income reduction but not consumption, which may suggest that climate shocks affect households directly by reducing their income, but also indirectly by raising food prices.
Keywords: N36; O12; O15; 330; Zambia; climate shocks; labour; gender; consumption